On The Edge Irregularity Strength of Firecracker Graphs F2,m - Rismawati Ramdani; Desi Laswati Suwandi (KUBIK, 2022)
Let  be a graph and k be a positive integer. A vertex k-labeling  is called an edge irregular labeling if there are no two edges with the same weight, where the weight of an edge uv is . The edge irregularity strength of G, denoted by es(G), is the minimum k such that  has an edge irregular k-labeling. This labeling was introduced by Ahmad, Al-Mushayt, and Bacˇa in 2014.  An (n,k)-firecracker is a graph obtained by the concatenation of n k-stars by linking one leaf from each. In this paper, we determine the edge irregularity strength of fireworks graphs F2,m.